2021
DOI: 10.3390/polym13244369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Properties of New Polymeric Monometallic Composites Based on Copolymers of Polypropylene Glycol Maleate Phthalate with Acrylic Acid

Abstract: Metal-polymer composites based on copolymers of polypropylene glycol maleate phthalate with acrylic acid and metallic nickel and silver were synthesized for the first time. The objects obtained were characterized by infrared (IR) and Raman spectroscopies, thermogravimetry, a scanning electron microscope with energy dispersive spectroscopy, and atomic emission spectrometry. The catalytic activity of new metal-polymer composites that exhibited a rather high efficiency in the reactions of electrocatalytic hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It has been established that the presence of a RAFT agent affects both the density of the polymer network and the formation of a branched polymer. The obtained results showed that the synthesized crosslinked copolymers have high sorbing properties and indicate the possibility of their use as smart systems, as well as efficient nanocatalysts [15]. In this work, it seemed interesting to investigate in detail the direction of the copolymerization reaction of p-PGM with AA depending on the concentration of the RAFT agent.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that the presence of a RAFT agent affects both the density of the polymer network and the formation of a branched polymer. The obtained results showed that the synthesized crosslinked copolymers have high sorbing properties and indicate the possibility of their use as smart systems, as well as efficient nanocatalysts [15]. In this work, it seemed interesting to investigate in detail the direction of the copolymerization reaction of p-PGM with AA depending on the concentration of the RAFT agent.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of metal-filled hydrogels lies in the fact that they combine the properties of the hydrogel matrix and the metal filler. The introduction of metal particles of various nature into the structure of hydrogels provides them with new properties, including bactericidal and antifungal [ 43 ], optical [ 44 ], catalytic [ 45 ], electrical [ 46 ], and magnetic [ 47 ] properties, as well as the possibility of changing these properties in the desired direction. Metal-filled hydrogels differ from other metal-filled polymer materials in their ability to change conductive characteristics depending on temperature, pH medium, moisture, and the content of low molecular weight substances, which provides the possibility of their use in the manufacture of various types of detectors and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…There is an apparent explanation for that, their factor contributes to a significant simplification and reduction in the cost of the work process, an increase in product quality, and production without harming the health of employees and the environment [ 7 , 8 ]. These properties are primarily expressed in polyester resins, thereby they appear in polycondensation polymers quite clearly [ 9 , 10 , 11 , 12 ]. All this has led to active growth in their use and to the emergence of a wide range of fundamentally new methods of production, processing, and use [ 13 ].…”
Section: Introductionmentioning
confidence: 99%